Exploitation of lichens as a source of novel natural products - Witts, Jessica Katherine (2022)
Lichens can be described as an obligate mutualistic symbiosis, usually between an ascomycete fungus (the mycobiont) and either a green alga and/or cyanobacterium (the photobiont), in which a unique thallus structure is formed. Fungal species which follow this evolutionarily successful lifestyle are known to produce a diverse range of secondary metabolites, many of which are unique to lichens and are not found to be produced in other non-lichen fungal species. Lichen secondary metabolites, the majority of which are thought to be produced by the fungal partner, possess a variety of biological activities and, therefore, have the potential for biotechnological and industrial applications. However, the extremely slow growth rate associated with lichens hampers their biotechnological exploitation as it is neither feasible nor sustainable to produce lichen secondary metabolites on an industrial scale. Thus, alternative methods are required for the production of lichen secondary metabolites. This study used two approaches in an attempt to overcome this problem. The first approach involved the use of UV mutagenesis to create mutants of various lichen mycobionts (Xanthoria parietina, Lecanora chlarotera and Amandinea punctata) possessing a faster growth rate. It was planned to analyse these mutants at the genomic level in order to obtain insights into the mutations supporting higher growth rates. However, although results obtained in this study showed that exposure of X. parietina ascospores to UV-C appeared to produce potentially faster-growing mutants with at least an incremental increase in growth rate, only pilot work was conducted in this study and further elucidation of the genetic basis of this increased growth rate is required. The second approach used in this study to achieve the production and characterisation of lichen-derived secondary metabolites was that of the heterologous expression of lichen secondary metabolism genes in the non-lichen fungal expression platform strains Aspergillus niger ATNT16 and Aspergillus oryzae OP12. The heterologous expression of two types of lichen secondary metabolism genes, those encoding polyketide synthases and non-ribosomal peptide synthetase-like enzymes, was attempted. A number of polyketide products have been described from lichens, the biosynthesis of some of which are restricted to lichen species. Conversely, no metabolites originating from NRPS-like enzymes have been described from lichens, but the enzymes are conserved. The results obtained here demonstrate that heterologous expression of lichen secondary metabolism genes is an appropriate method for the production of certain lichen-derived secondary metabolites. When focussing on lichen-derived PKS genes, four genes from Cladonia grayi, two genes from Evernia prunastri and one gene from Usnea longissima were selected for expression studies. These studies resulted in the functional heterologous expression of two PKS genes from C. grayi (Clagr3.6 and Clagr3.21), with the Clagr3.6 enzyme being identified as a 1,3,6,8-tetrahydroxynaphthalene synthase and the Clagr3.21 enzyme awaiting characterisation. However, it was observed that metabolite production was only successful for these lichen-derived genes at 23 °C, suggesting that these lichen secondary metabolism proteins are temperature-sensitive. Unfortunately, attempts to achieve the functional heterologous expression of the PKS genes from E. prunastri and U. longissima were unsuccessful. Attempts to achieve the functional expression of NRPS-like enzymes focussed on two genes from C. grayi and three genes from E. prunastri. Similarly to the results obtained for PKS expression, the functional heterologous expression of the three NRPS-like enzymes from E. prunastri was not achieved. However, we were able to achieve the functional expression of both NRPS-like genes (Clagr3.11 and Clagr3.30) selected from C. grayi. The Clagr3.30 enzyme was identified as a typical atromentin synthetase, but again was only active at a low temperature. Interestingly, the Clagr3.11 enzyme was found to produce three metabolites, which suggests that the enzyme possesses a flexible substrate specificity. The discovery of this enzyme gives the first example of an NRPS-like enzyme that is not only able to accept various substrates, but is also capable of producing metabolites from mixed substrates, including from non-natural substrates such as 4-chloro-phenylpyruvate; in vitro studies using the Clagr3.11 enzyme confirmed this. Further studies using Clagr3.11, in which the adenylation domain of this enzyme was fused with the thiolation and thioesterase domains of an Aspergillus brasiliensis atromentin synthetase, also resulted in successful metabolite production; this demonstrates that it is feasible to use Clagr3.11 in domain fusion experiments. Furthermore, the Clagr3.11 enzyme differed from that of the Clagr3.30, Clagr3.6 and Clagr3.21 enzymes in the sense that metabolite production was achieved at both 23 °C and 28 °C, indicating a reduced temperature sensitivity of this enzyme. The discovery of the first NRPS-like enzyme with a flexible substrate specificity is particularly noteworthy, as it provides the opportunity to use this enzyme for the production of novel natural products not found in nature. This would perhaps allow the creation of natural products which possess enhanced or novel biological activities, which could therefore have pharmaceutical applications. The successful heterologous production of these lichen-derived secondary metabolites at 23 °C, and the subsequent suggestion that lichen secondary metabolism proteins may be temperature-sensitive, implies that a relatively low growth temperature is of high importance for the successful heterologous production of lichen-derived metabolites. Further investigation of the heat sensitivity of lichens appeared to confirm this observation, with lichen primary metabolism proteins also appearing to show sensitivity to higher temperatures. This has important implications for future attempts to achieve metabolite production from lichen-derived genes in heterologous hosts, as the low temperatures favoured for production of lichen-derived proteins is not compatible with the growth of established expression platforms, such as A. niger and A. oryzae, currently used for heterologous protein production. Therefore, the development of a psychrotolerant expression platform may be of particular advantage for future studies involving the heterologous production of lichen-derived proteins.